bwFDM Communities – a Research Data Management Initiative in the County of Baden-Wuerttemberg, Germany - Pappenberger, Karlheinz (Septentrio Conference Series, 2014)
>> See video of presentation (33 min.) On 29th July 2014 the Ministry of Science, Research and the Arts of Baden-Wuerttemberg, Germany, has launched an e-science initiative to build up a powerful, efficient and innovative information infrastructure for all universities, research institutions and universities of applied science of the county of southwest Germany. With the overall budget of 3.7 million euro action plans within the five areas licensing, digitalization, research data management, open access and virtual research environments shall be worked out within the next years. Within this framework an 18-month project has been launched at the beginning of 2014 to evaluate the needs of services and support libraries and IT service centres should offer for researchers in the area of research data management. In this “bwFDM communities” named project full time key accounters have been established at all 9 universities of the county (Freiburg, Heidelberg, Hohenheim, Karlsruhe, Konstanz, Mannheim, Stuttgart, Tuebingen and Ulm; among them national and international highly ranked universities). The task of the key accounters is to identity concrete needs and requirements of all research groups working with research data (in a broad sense including all areas of science, social science and humanities) at each of the nine universities as well as possible solutions by conducting semi-structured personal interviews and documenting them in the form of user stories. As a result issues of importance and requirements will be identified, categorized and finalized to recommendations for concrete action plans. The presentation will give an overview of the first results of the project, thereby also highlighting the roles libraries and IT service centres are expected to play from the researcher´s point of view. Furthermore the presentation will point out the response of the University of Konstanz Library to the rising awareness of the importance of research data within the University Executive, showing the special efforts the University of Konstanz Library undertakes to support researchers in their research data management so far and to build up more and more expertise in the area of research data management. One step had been the set-up of a disciplinary data repository in the field of ornithology (Movebank data repository).